International network for acid prevention progress towards a global organization - R. Gallinger (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
In 1997, a group of Canadian mining companies met to review the Mine Environment Neutral Drainage (MEND) program and to consider future activities. They concluded that (1) that Canadian industry and Natural Resources Canada (NRCan) should fund a small secretariat in Ottawa to support technology transfer in Canada and, (2) that it was important for industry to continue the momentum of MEND on an international scale. The need for the International Network for Acid Prevention (INAP) was strongly endorsed by consultants, company, university, and government experts from Australia, Canada, and the United States who convened in Vancouver in February 1998. The initial focus was the development of a solid knowledge base covering the collective experience of INAP?s members to promote the dissemination of successful practices, the identification of knowledge gaps, and the formulation of effective research proposals. The sharing of information on past successes and failures alone was viewed as sufficient justification for the formation of INAP. INAP was officially launched in October 1998, and is now an effective, industry-based initiative to globally coordinate research and development in the management of sulphide mine waste. Significant improvements in the management of sulphidic mine materials through knowledge sharing, research, and development of technology by INAP will reduce liability associated with acid drainage. This paper will explore the international efforts and activities of INAP